Entrepreneurial Characteristics, Motivation and Skills as Supporting Business Success - Rivaldo Alessandro Azarya Paat; Hani Sirine (Universitas Serambi Mekkah, 2023)
Franchising is one way that can be done to provide business opportunities for business actors in the region. This study aims to find out what the characteristics, motivation and entrepreneurial skills are like as a support for the success of the Janji Jiwa Coffee Franchise business in Tomohon City. To achieve the research objectives, a qualitative approach was used by conducting online interviews with business owners, employees and customers. The results of this study indicate that business success can be seen from the addition of employees, increase in income, increase in the amount of production, increase in the number of means of production, job satisfaction, and consistency in work. The results of the study also found that there were indicators in entrepreneurial characteristics, such as attitude, character, intelligence, knowledge and consistency. Entrepreneurial motivation is measured through entrepreneurial encouragement, utilizing internal capacity, generating profits, and opening new jobs. The entrepreneurial skills can be seen from relational skills, decision-making skills, leadership skills, as well as managerial skills and creativity.